Intra-dialytic hypotension following the transition from continuous to intermittent renal replacement therapy - Beaubien-Souligny, William; Yang, Yifan; Burns, Karen E. A.; Friedrich, Jan O.; Meraz-Muñoz, Alejandro; Clark, Edward G.; Adhikari, Neill K.; Bagshaw, Sean M.; Wald, Ron (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Transition from continuous renal replacement therapy (CRRT) to intermittent renal replacement therapy (IRRT) can be associated with intra-dialytic hypotension (IDH) although data to inform the definition of IDH, its incidence and clinical implications, are lacking. We aimed to describe the incidence and factors associated with IDH during the first IRRT session following transition from CRRT and its association with hospital mortality. This was a retrospective single-center cohort study in patients with acute kidney injury for whom at least one CRRT-to-IRRT transition occurred while in intensive care. We assessed associations between multiple candidate definitions of IDH and hospital mortality. We then evaluated the factors associated with IDH. Results We evaluated 231 CRRT-to-IRRT transitions in 213 critically ill patients with AKI. Hospital mortality was 43.7% (n = 93). We defined IDH during the first IRRT session as 1) discontinuation of IRRT for hemodynamic instability; 2) any initiation or increase in vasopressor/inotropic agents or 3) a nadir systolic blood pressure of < 90 mmHg. IDH during the first IRRT session occurred in 50.2% of CRRT-to-IRRT transitions and was independently associated with hospital mortality (adjusted odds ratio [OR]: 2.71; CI 1.51–4.84, p < 0.001). Clinical variables at the time of CRRT discontinuation associated with IDH included vasopressor use, higher cumulative fluid balance, and lower urine output. Conclusions IDH events during CRRT-to-IRRT transition occurred in nearly half of patients and were independently associated with hospital mortality. We identified several characteristics that anticipate the development of IDH following the initiation of IRRT.